- #1
mathmari
Gold Member
MHB
- 5,049
- 7
Hey!
We are given the polynomial functions $$T_0(x)=1, T_1(x)=x, x \in \mathbb{R} \\ T_{n+1}(x)=2xT_n(x)-T_{n-1}(x), n \in \mathbb{N}, x \in \mathbb{R}$$
(Chebyshev polynomials)
Using induction I have to show that:
We are given the polynomial functions $$T_0(x)=1, T_1(x)=x, x \in \mathbb{R} \\ T_{n+1}(x)=2xT_n(x)-T_{n-1}(x), n \in \mathbb{N}, x \in \mathbb{R}$$
(Chebyshev polynomials)
Using induction I have to show that:
- the degree of $T_n$ is $n$
- $\forall n \in \mathbb{N}$ : $T_n(1)=1$ and $T_n(-1)=(-1)^n$
- for the polynomial function $T_n$ with $n \in \mathbb{N}$ the coefficient of the highest power of $x$ is $a_n=2^{n-1}$
- for all $x \in \mathbb{R}$ and $n \in \mathbb{N}$ it holds that $T_n(-x)=(-1)^nT_n(x)$
- Base Case:
$n=0$ : $deg(T_0(x))=deg(1)=0$
$n=1$ : $deg(T_1(x))=deg(x)=1$ Inductive hypothesis:
We suppose that it holds for all $i$, $2 \leq i \leq n$. So, for $2 \leq i \leq n$ we have that $deg(T_i(x))=i$.
Inductive step:
We want to show that it stands for $n+1$.
$T_{n+1}(x)=2xT_n(x)-T_{n-1}(x)=2(\text{ polynomial of degree} 1)(\text{ polynomial of degree }n)-(\text{ polynomial of degree }n-1)=\text{ polynomial of degree } n+1$ Is this correct? Is there a better way to formulate it?
- Base Case:
$n=0$ : $T_0(1)=1$
$n=1$ : $T_1(1)=1$Inductive hypothesis:
We suppose that it holds for all $i$, $2 \leq i \leq n$. So, for $2 \leq i \leq n$ we have that $T_i(1)=1$.
Inductive step:
We want to show that it stands for $n+1$.
$T_{n+1}(1)=2 \cdot 1 \cdot T_n(1)-T_{n-1}(1)=2-1=1$
- Base Case:
$n=0$ : $T_0(-1)=1$
$n=1$ : $T_1(-1)=-1$Inductive hypothesis:
We suppose that it holds for all $i$, $2 \leq i \leq n$. So, for $2 \leq i \leq n$ we have that $T_i(-1)=(-1)^i$.
Inductive step:
We want to show that it stands for $n+1$.
$T_{n+1}(-1)=2 \cdot(-1) \cdot T_n(-1)-T_{n-1}(-1)=-2(-1)^n-(-1)^{n-1}=-2(-1)^n+(-1)^{n}=-(-1)^n=(-1)^{n+1}$
Is this correct?
- Base Case:
- Base Case:
$n=1$ : $T_1(x)=x \Rightarrow a_1=1=2^{1-1}$ Inductive hypothesis:
We suppose that it holds for all $i$, $2 \leq i \leq n$. So, for $2 \leq i \leq n$ we have that $a_i=2^{i-1}$.
Inductive step:
We want to show that it stands for $n+1$.
$T_{n+1}(x)=2xT_n(x)-T_{n-1}(x)=2x(2^{n-1}x^n+\dots )-(2^{(n-1)-1}x^{n-1})=2^nx^{n+1}+\dots \Rightarrow a_{n+1}=2^n$
Is this correct? Is there a better way to formualte it?
- Base Case:
$n=0$ : $T_0(-x)=1=(-1)^0T_0(x)$
$n=1$ : $T_1(-x)=-x=(-1)^1T_1(x)$ Inductive hypothesis:
We suppose that it holds for all $i$, $2 \leq i \leq n$. So, for $2 \leq i \leq n$ we have that $T_i(-x)=(-1)^iT_i(x)$.
Inductive step:
We want to show that it stands for $n+1$.
$T_{n+1}(-x)=2(-x)T_n(-x)-T_{n-1}(-x)=-2x(-1)^nT_n(x)-(-1)^{n-1}T_{n-1}(x)=2x(-1)^{n+1}T_n(x)-(-1)^{n-1}(-1)(-1)T_{n-1}(x)=2x(-1)^{n+1}T_n(x)-(-1)^{n+1}T_{n-1}(x)=(-1)^{n+1}\left (2xT_n(x)-T_{n-1}(x)\right )=(-1)^{n+1}T_{n+1}(x)$
Is this correct? Is there a better way to formulate it?